Polyrotaxane Nanocarriers Can Deliver CRISPR/Cas9 Plasmid to Dystrophic Muscle Cells to Successfully Edit the DMD Gene. Issue 7 (3rd June 2019) - Emami, Michael R.; Young, Courtney S.; Ji, Ying; Liu, Xiangsheng; Mokhonova, Ekaterina; Pyle, April D.; Meng, Huan; Spencer, Melissa J.
Abstract: Gene editing with clustered regularly interspaced short palindromic repeats and CRISPR‐associated protein 9 (CRISPR/Cas9) has shown promise in models of Duchenne muscular dystrophy (DMD); however, nonviral strategies to deliver CRISPR to muscle have not been widely explored or optimized. Most studies have relied on viral vectors, which are likely limited to single dosing due to their immunogenicity, thus reducing their therapeutic potential. Therefore, there is a need to develop nonviral approaches that allow for delivery and repeat dosing of CRISPR/Cas9 therapies to skeletal muscle. Here, biocompatible multi‐arm polyrotaxane (PRX) nanocarriers, are iteratively optimized for packaging large plasmid DNA for delivery to muscle cells. The PRXs are optimized by addition of a disulfide‐responsive linker that enhances plasmid release. Furthermore, conjugation of peptides leads to quicker uptake and improved transfection efficiency in humanized dystrophic muscle cells in vitro. Finally, in vitro delivery of PRXs complexed with a CRISPR/Cas9 platform demonstrates effective deletion of DMD exons 45–55, a therapeutic strategy with potential to restore the reading frame for half of DMD patients. This work represents the first PRX platform that is optimized and designed for delivery of large plasmid DNA, such as CRISPR/Cas9, to dystrophic muscle cells. Abstract : Novel multi‐arm polyrotaxane (PRX) nanoparticles are iteratively optimized to deliver large plasmid DNA, including CRISPR/Cas9, to primary dystrophic muscle cells derived from a humanized mouse model of Duchenne muscular dystrophy (DMD). The multi‐arm PRXs are optimized for enhanced cellular uptake and plasmid release to achieve CRISPR‐mediated gene editing to restore the DMD reading frame in muscle in vitro.